Water Resources Management. Innovative and Green Solutions. - Brears, Robert C. (De Gruyter, 2021)
Water resources management consists of planning, developing, distributing, and managing available water resources. With increasing climatic and non-climatic challenges, optimised water management becomes more demanding. This book presents innovative solutions to these challenges in the areas of water conservation, recycling, and reuse, recovery of resources from wastewater, protection of water quality, and smart water management. It also presents innovative financial solutions to meet water challenges globally.
Keywords: Wasserressourcen; Ressourcenmanagement; Wasserknappheit; Wasserrecycling; Abwasseraufbereitung; Grauwasser; Energiegewinnung; Staudamm; Wassermanagement; Digitalisierung; Finanzierungsmöglichkeit; Grundwasserschutz; Gewässerschutz; Best Practice